ABSORPTIVE CAPACITY AND THE INTERNATIONALIZATION PROCESS OF AN EMERGING MULTINATIONAL - Martignago, Graciella; Cário, Silvio Antônio Ferraz; Alperstedt, Graziela Dias (Revista de Negócios, 2018)
Based on an evolutionary approach to international expansion and learning by a firm, the purpose of this study is to explain the absorptive capacity of knowledge for the internationalization process of emerging multinational companies. A qualitative study was conducted, which was inductive, descriptive and longitudinal, based on a case study of biggest cement company of South America. The study identified the previous knowledge, the new knowledge and described the acquisition process of knowledge, the transformation and the exploitation process involved in the internationalization. This study showed that even a mature company, leader in its home market, with experience in competition with the main international players, it needed to acquire new knowledge about Â internationalization. The assimilation of knowledge was hampered by the prior knowledge structure and new routines were created before the external direct investment materialized. After the acquisition in the foreign market, the adaptation of routines created in the domestic market was developed.